Technical aspects of stapled hepatectomy in liver surgery: how we do it - Mehrabi, Arianeb; Hoffmann, Katrin; Nagel, Alexander Johannes; Ghamarnejad, Omid; Khajeh, Elias; Golriz, Mohammad; Büchler, Markus W. (Journal of gastrointestinal surgery, 2019)
There are diverse approaches to parenchymal transection and the preferred approach remains controversial among liver surgeons. Stapling devices, which were initially established for vascular control, have been the standard parenchymal transection technique in many departments for more than 15 years. This article describes the technical aspects, tips, and tricks of stapled hepatectomy using right hemihepatectomy as an example. The existing literature on this topic is also reviewed.
Gesehen am 21.06.2019